Carrion Crow "Corvus Corone" breeding in Lubuskie Province, w Poland - Zduniak, Piotr; Czechowski, Paweł (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In 2013, a clutch of the Carrion Crow "Corvus corone" was recorded in the Warta Mouth National Park, western Poland. In April and the first half of May a female incubating two and later four eggs was observed. In mid-May the nest was found empty, indicating that the failure occurred during incubation or the early nestling stage. No male was observed until that time. However, two Carrion Crows were recorded near the nest after the breeding failure, which indicates that it was indeed a breeding attempt made by a homogamic ("pure") Carrion Crow`s pair. This is the first case described for the Lubuskie Province and the second for Poland in the last 200 years.
Keywords: wróblowe; ornitologia